2020
DOI: 10.30699/mmlj17.3.1.60
|View full text |Cite
|
Sign up to set email alerts
|

The effects of artichoke aqueous extract on the growth performance, intestinal morphology, and blood metabolites in broiler chickens

Abstract: An experiment was conducted to study the efficacy of artichoke aqueous extract (AAE) on the performance, carcass characteristics, clinical blood chemistry values, and the gut morphology of female broiler chickens poisoned with carbon tetra chloride (CCl 4 ). Broiler chicks were categorized into four experimental groups each of which contained 10 chicks; control group, artichoke group (0.5g/kg/bwt of artichoke aqueous extract), CCl 4 group (1ml/kg/bwt of CCl 4 ), and artichoke+ CCl 4 group (0.5g/kg/bwt of artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In coordination with our findings El-Maddawy and Ibraheim (2019) defined that the control boiler the cholesterol and triglyceride were greater up to 100.90 and 88.83mg/dI than 79.40 and 77.97mg/dI in the artichoke boiler, respectively. This is Confirmed by Karimi et al (2020) who reported that cholesterol and triglyceride concentration were more in the control boiler were 121.90 and 94.69 mg/dL than 110.67 and 90.72mg/dL in the artichoke boiler, respectively. The lowest LDL was observed in D1 rabbits compared with all other rabbits, then the same trend was recorded by Fallah et al (2013) who reported that LDL was 34.06 and 32.16 mgdI -1 in control and artichoke broiler, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In coordination with our findings El-Maddawy and Ibraheim (2019) defined that the control boiler the cholesterol and triglyceride were greater up to 100.90 and 88.83mg/dI than 79.40 and 77.97mg/dI in the artichoke boiler, respectively. This is Confirmed by Karimi et al (2020) who reported that cholesterol and triglyceride concentration were more in the control boiler were 121.90 and 94.69 mg/dL than 110.67 and 90.72mg/dL in the artichoke boiler, respectively. The lowest LDL was observed in D1 rabbits compared with all other rabbits, then the same trend was recorded by Fallah et al (2013) who reported that LDL was 34.06 and 32.16 mgdI -1 in control and artichoke broiler, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, the decreasing level of the liver enzymes (D1 rabbits) in the current study may reflect the decreased level of glucose (Noordam et al, 2017) revealing that the scientific concentrations of liver enzymes have been associated with glycaemia. Karimi et al (2020) found that lower AST and ALT in artichoke boiler were 72.41and 4.28 IU/L than 141.11 and 5.94 IU/L in the control group, respectively. Also, Abadjieva et al (2020) recorded that ALT and AST had more concentration in control up to 11.9 and 182.0 U/L than 10.9 and 160.0U/L in laying hens received 3 g/kg of milled artichoke.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations